-2(3s-4)-8=-3(6s+1)-5

Simple and best practice solution for -2(3s-4)-8=-3(6s+1)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3s-4)-8=-3(6s+1)-5 equation:


Simplifying
-2(3s + -4) + -8 = -3(6s + 1) + -5

Reorder the terms:
-2(-4 + 3s) + -8 = -3(6s + 1) + -5
(-4 * -2 + 3s * -2) + -8 = -3(6s + 1) + -5
(8 + -6s) + -8 = -3(6s + 1) + -5

Reorder the terms:
8 + -8 + -6s = -3(6s + 1) + -5

Combine like terms: 8 + -8 = 0
0 + -6s = -3(6s + 1) + -5
-6s = -3(6s + 1) + -5

Reorder the terms:
-6s = -3(1 + 6s) + -5
-6s = (1 * -3 + 6s * -3) + -5
-6s = (-3 + -18s) + -5

Reorder the terms:
-6s = -3 + -5 + -18s

Combine like terms: -3 + -5 = -8
-6s = -8 + -18s

Solving
-6s = -8 + -18s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18s' to each side of the equation.
-6s + 18s = -8 + -18s + 18s

Combine like terms: -6s + 18s = 12s
12s = -8 + -18s + 18s

Combine like terms: -18s + 18s = 0
12s = -8 + 0
12s = -8

Divide each side by '12'.
s = -0.6666666667

Simplifying
s = -0.6666666667

See similar equations:

| -4x-7y=6 | | (2x-7)-(x-3)=2 | | 3a-4b=8b | | 2n+13+n=93 | | 2n+13n=93 | | 2x+4x-1=11 | | 2.91-(-0.2)= | | -7+(-32)-12+5= | | x^2-3=77 | | 6x-3(6x-3)=93 | | .08(24)+.02x=.04(12+x) | | 5-2x=4x+41 | | 2-x=9x+2 | | 5x+2-7x=7-(2x+5) | | x^4-8x^3+18x^2-27=0 | | -9x-8y=8 | | 3x^3= | | 8x-1=8(x+1) | | -1+2+(-7)= | | 7x-(9x+5)=6x-21 | | -16.4+18.1= | | 28(y+2)=4(6y+7) | | 7x-(2x+15)=20 | | 60=3x+2x+3+1 | | 9+(-5)= | | -163+8x+x=44 | | 5(m+4)=8(m-2) | | 3x^3+44x^2+127x+60=0 | | -2x+11=6x-13 | | 4x^2+25=-20x | | 6x+9x=45 | | x=-181+95 |

Equations solver categories